2013
DOI: 10.1111/jar.12037
|View full text |Cite
|
Sign up to set email alerts
|

Different Factors Influence Self‐Reports and Third‐Party Reports of Anger by Adults with Intellectual Disabilities

Abstract: Service users and their carers appear to use different information when rating the service users' anger. Service users' self-ratings reflect their internal emotional state and mental health, as reflected by their ratings of anxiety and depression, whereas staff rate service users' anger on the basis of overt behaviours, as measured by challenging behaviour scales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…3,33 An analysis of our baseline data established that service users' self-ratings of anger are related to other self-ratings of mental health status, whereas carers' ratings of service-user anger are related to their ratings of observed challenging behaviour. 34 This may explain why keyworkers reported larger effects, as service users showed clear differences on a number of behavioural outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…3,33 An analysis of our baseline data established that service users' self-ratings of anger are related to other self-ratings of mental health status, whereas carers' ratings of service-user anger are related to their ratings of observed challenging behaviour. 34 This may explain why keyworkers reported larger effects, as service users showed clear differences on a number of behavioural outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Rose et al . (in press) found that proxies use different information when rating a person with ID's emotions compared with individuals' with ID self‐reports of their internal states. Nevertheless, many people with ID experience cognitive and language impairments that result in difficulty understanding questions and communicating reliable answers (Finlay & Lyons ; Perry & Felce ).…”
Section: Introductionmentioning
confidence: 99%
“…This proposition is supported by Rose et al . (), who showed that clients rate their own behaviour on the basis of their internal feelings and mental health, as reflected by their ratings of anxiety and depression. Support staff rate clients' CB based on overt behaviours.…”
Section: Discussionmentioning
confidence: 99%